Pocahontas Goes to the Clinic: Popular Culture as Lingua Franca in a Cultural Borderland - Mattingly, Cheryl (2008)
Urban hospitals constitute an example of what is arguably the most visible site in anthropology these days—the border zone. Negotiating health care requires trafficking in tricky spaces where patients and their families must pay vigilant attention about when to submit, when to resist, and how to collaborate. Drawing from ethnographic research carried out over the past nine years among African American families who have children with severe illnesses and disabilities, I examine how children's popular culture operates in the fraught borderland that constitutes the urban clinic. Global icons like a Disneyfied Pocahantas can function as a lingua franca, offering a language of publicly available symbols on which families, health professionals, and children can draw to create a shared imaginative space across race and class divides and across the sometimes even more radical divide between sufferer and healer.